ANALISIS FISIKA KIMIA DARI KERANG DARA (Anadara granosa) YANG BERASAL DARI KAYUTANYO KAB. BANGGAI The Analysis of physical chemical from dara shells (Anadara granosa) origin from Kayutanyo, Kab.Banggai - SULASMI ANGGO (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2017)
The Analysis of physical chemical from dara shells (Anadara granosa) origin from Kayutanyo, kab. Banggai, has been conducted.Dara shell meat is sleaned and dried and after that powered with blender. Determine % rendement, water bonding capacity and index water solubility with Anderson method, coarse fat content with gravimetric method and carbohydrate method with “bye difference” decrease method.The result of analysis showed rendement value is 24,35%, water bonding capacity is 1,6248 gram/ml, index water solubility is 0,202 gram/ml, water content is 79,0045%, total dust content is 1,072%, coarse protein content is 2,25%, coarse fat content is 8,47%, carbohydrate content is 9,2035%. Keyword : Dara shells, (Anadara granosa), analysis physical chemical